2018
DOI: 10.1002/wat2.1282
|View full text |Cite
|
Sign up to set email alerts
|

Opening the black box of spring water microbiology from alpine karst aquifers to support proactive drinking water resource management

Abstract: Over the past 15 years, pioneering interdisciplinary research has been performed on the microbiology of hydrogeologically well‐defined alpine karst springs located in the Northern Calcareous Alps (NCA) of Austria. This article gives an overview on these activities and links them to other relevant research. Results from the NCA springs and comparable sites revealed that spring water harbors abundant natural microbial communities even in aquifers with high water residence times and the absence of immediate surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 127 publications
0
39
1
Order By: Relevance
“…In the last decade, several studies using molecular surveys have described the microbial diversity of karst systems 14 . Surprisingly, most of the phylotypes affiliated to Nitrospirae in the core community were not closely related (identity <97%) to 16S rRNA gene sequences reported in this and other studies and likely represent previously undescribed bacterial species.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In the last decade, several studies using molecular surveys have described the microbial diversity of karst systems 14 . Surprisingly, most of the phylotypes affiliated to Nitrospirae in the core community were not closely related (identity <97%) to 16S rRNA gene sequences reported in this and other studies and likely represent previously undescribed bacterial species.…”
Section: Discussioncontrasting
confidence: 60%
“…Therefore, to survive in these extreme habitats they may have developed specific functions and adopted a chemolithotrophic lifestyle using inorganic resources to provide them with the energy and nutrients necessary for survival 13 . The microbial composition of groundwaters and their stability with time are good indicators of ecosystem confinement and of the good quality of resource management 14 . Some studies have shown a direct impact on groundwater microbial communities with the modification of discharge conditions, or long‐term diversity changes after drilling 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Karst rivers are commonly regulated by damming, yet the influence of these dams on changes in hydrological series of water discharge is negative or positive (Miao, Ni, Borthwick, & Yang, ). Although the diversity and dynamics of microbes in karst springs (Farnleitner et al., ; Ohad et al., ; Savio et al., ), unsaturated and saturated karst aquifers (Cooper et al., ; Gray & Engel, ; Johnson et al., ; Lin et al., ; Menning et al., ), and water pools (Shabarova et al., ) as well as in groundwater‐surface water exchange systems (Li, Song, et al., ) have been discussed in the literature, much less attention has been paid to the structure of bacterioplankton communities in dammed karst rivers. In addition, previous studies on bacterioplankton communities in the canyon‐shaped and meso‐eutrophic Rimov Reservoir (Simek et al., ), the dammed Ebro River (Ruiz‐González, Proia, Ferrera, Gasol, & Sabater, ), and the rivers controlled by the Three Gorges Dam (Huang et al., ; Li, Lu, et al., ; Yan et al., ) did not include the seasonal variation or depth dynamics in bacterioplankton.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the sources of fecal pollution in the water resource, as originally determined by standardized SFIB assays, can be an essential part for system assessment (i.e. water safety planning, sanitation safety planning), target-oriented catchment management, and finally, can serve also as a very important starting point for hazard-and risk assessment and MST-guided QMRA (Savio et al, 2018).…”
Section: Implications For Practitioners and Catchment And Risk Managementioning
confidence: 99%
“…Thus, water resources from (alpine) karst aquifers require sustainable protection from fecal pollution within the catchment and proper microbial quality management at and after the spring (e.g. optimized spring water abstraction, adjusted treatment and disinfection measures) if used for drinking water supply (Farnleitner et al, 2018;Savio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%